Keikutsertaan Pekerja Informal dalam JPKM Sebagai Upaya Promosi Kesehatan di Kecamatan Kejobong Kabupaten Purbalingga - Widiastuti, Indiyah; Suryoputro, Antono; Mustofa, Syamsulhuda Budi (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
Community Health Care Insurance (JPKM) has been developed since 1992 and it is the embryo of National Social Security System based on Acts No.40 year 2004. Purbalingga is a district in Indonesia has developed JPKM since 2002 and has commitment to reach universal coverage by the year 2012. This research aims to analyze several factors that influence the informal community participation on JPKM Kejobong, Purbalingga. Survey method used cross sectional approach. Sample making through random proportional technique with amount 100 respondents. Data processing attained through quantitative univariat, bivariat and multivariat method. While data analyze used logistic regression with chi square test. The research results show that JPKM coverage among informal community in Kejobong still low (43%) and 57% respondents not enrolled. The reasons not enrolled respondents are inability (42.1%), knowledge (21.1%), poor public health service (22.8%) and others (14%). Factors proved influence are amount of family, knowledge, attitude and cadre role.Â